Influence of the scale range width on the determination of the hydraulic conductivity and effective porosity. The case of a porous aquifer in southern Italy - Fallico, Carmine; De Bartolo, Samuele; Rivera-Velasquez, María Fernanda; Ianchello, Mario (ACI Avances en Ciencias e Ingenierías, 2019)
AbstractThe importance of a law that, for an assigned porous medium, gives the variability of the hydraulic conductivity with the effective porosity is well known. Commonly this variability is represented by a power law at different scales, especially those of laboratory and field. Often it can be useful to have a scaling law valid for a single scale range, comprising both those of laboratory and field. Therefore investigation about the reliability of the laws representing the scaling behavior in the various intervals to which reference was made could be suitable.The purpose of this study is to provide evidence about the reliability of the scaling laws for laboratory, field and global (laboratory plus field) scaling ranges, verifying consistency with the expected proportionality between hydraulic conductivity and effective porosity for each of these. This verification was carried out using power-type scaling laws to two and four parameters respectively, and performing suitable moving averages of original data sets, in an attempt to reduce the inevitable measurement uncertainties. The experimental results, obtained with reference to the confined aquifer of Montalto Uffugo test field, show that there are no significant differences between the scaling laws considered and highlight the need to reduce the measurement uncertainties, which weigh heavily on the reliability of scaling laws. Keywords: Scaling law; Hydraulic conductivity; Effective porosity; Laboratory measurement, Field measurement. INFLUENCIA DE LA AMPLITUD DEL INTERVALO DE ESCALA EN LA DETERMINACIÓN DE LA CONDUCTIVIDAD HIDRÁULICA Y LA POROSIDAD EFECTIVA. EL CASO DE UN ACUÍFERO POROSA DEL SUR DE ITALIA La importancia de una ley que, para un dado medio poroso, describa la variabilidad de la conductividad hidráulica en función de la porosidad efectiva es bien conocida. Frecuentemente esta variabilidad está representada por una ley de potencia a diferentes escalas, especialmente las de laboratorio y de campo. A menudo es útil tener una ley de escalamiento válida para un cierto rango de escala incluyendo los de laboratorio y campo. Por esta razón, es oportuno investigar la confiabilidad de las leyes que representan este comportamiento de escalamiento en los diferentes intervalos a los cuales típicamente se hace referencia. El propósito de este estudio es proporcionar evidencia sobre la confiabilidad de las leyes de escalamiento para intervalos de escala válidos para laboratorio, campo y globales (laboratorio + campo), verificando la consistencia con la proporcionalidad esperada entre la conductividad hidráulica y la porosidad efectiva para cada uno de estos. Esta verificación se llevó a cabo utilizando leyes de escalamiento de potencia para dos y cuatro parámetros respectivamente, y tratando de reducir las inevitables incertidumbres de medición. Los resultados experimentales obtenidos con referencia al acuífero confinado del campo de prueba Montalto Uffugo, muestran que no hay diferencias significativas entre las leyes de escalamiento consideradas y se destaca la necesidad de reducir las incertidumbres de medición, las cuales tienen un alto peso sobre la fiabilidad de las leyes de escala. Palabras clave: ley de escalamiento; Conductividad hidráulica; porosidad efectiva; mediciones de laboratorio, medición de campo.